2023
DOI: 10.1002/adts.202200821
|View full text |Cite
|
Sign up to set email alerts
|

Physical Insights on the Phonon Dispersion of TiS2

Abstract: Titanium disulfide is a quasi-2D transition-metal dichalcogenide relevant for various potential applications. To exploit its technological capabilities, it is important to determine its fundamental properties including the lattice dynamics. The TiS 2 phonon dispersion curves available to date do not reproduce properly the experimental data for several reasons: i) all available experimental data are not taken into consideration, thus poor theory-experiment agreements have been obtained; ii) the (unknown) freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 37 publications
(70 reference statements)
1
10
0
Order By: Relevance
“…Our theoretical model assuming an ideal structure of 1 T -TiS 2 (see Section ) provides a qualitative explanation for the presence of the high-energy shoulder, as typically observed in the high-energy side of the A 1g band, as well as its intensity increase with the temperature. , However, independent spectroscopic and microscopic experiments indicate that realistic TiS 2 samples are nonstoichiometric, and their actual formula is Ti 1+ x S 2 where x is a positive numbertypically in the range of 2–4%. ,,,, The excess titanium appears as additional Ti atoms inside the van der Waals gaps . As interlayer titanium atoms have been one of the most often cited hypotheses of the “shoulder” band’s formation in Raman spectra of TiS 2 , ,,, the impact of this defect on phonons in TiS 2 deserves separate consideration.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…Our theoretical model assuming an ideal structure of 1 T -TiS 2 (see Section ) provides a qualitative explanation for the presence of the high-energy shoulder, as typically observed in the high-energy side of the A 1g band, as well as its intensity increase with the temperature. , However, independent spectroscopic and microscopic experiments indicate that realistic TiS 2 samples are nonstoichiometric, and their actual formula is Ti 1+ x S 2 where x is a positive numbertypically in the range of 2–4%. ,,,, The excess titanium appears as additional Ti atoms inside the van der Waals gaps . As interlayer titanium atoms have been one of the most often cited hypotheses of the “shoulder” band’s formation in Raman spectra of TiS 2 , ,,, the impact of this defect on phonons in TiS 2 deserves separate consideration.…”
Section: Resultsmentioning
confidence: 80%
“…29 Therefore, further study is needed to fully understand the temperature-induced blue shift of the reported "shoulder" band. 15,16 Recently, 28 an explanation has been proposed which assumes that the thermally-or intercalationinduced enlargement of the interlayer distance might lead to a motion of the Ti i atoms from the high-symmetry (0, 0, 1/2) positions to lower-symmetry positions�located closer to one of the layers. This was expected to stiffen the split A 1g -like phonon modes and increase the "shoulder" band's frequency.…”
Section: Phonons In Nonstoichiometric Tismentioning
confidence: 99%
See 1 more Smart Citation
“…Given the weak vdW interaction in the interface, Grimme’s method is employed to simulate the effect of the interlayer vdW force in phonon dispersion calculation. It is worth mentioning that even though some materials have vdW interactions, no trace of them can be found in the experimental data, which may be related to their inherently weak nature . But, compared with the general layered structure, the interface interaction of the Janus-based heterostructure is stronger, which is determined by the intrinsic dipole moment of the Janus monolayer .…”
Section: Resultsmentioning
confidence: 95%
“…It is worth mentioning that even though some materials have vdW interactions, no trace of them can be found in the experimental data, which may be related to their inherently weak nature. 31 But, compared with the general layered structure, the interface interaction of the Janus-based heterostructure is stronger, which is determined by the intrinsic dipole moment of the Janus monolayer. 32 We present phonon dispersion relations of GaS/SWSe (Figure 1c) and GaS/SeWS (Figure 1d) heterostructures, indicating that the flipping of Janus monolayers has little effect on the vibrational properties of heterostructures.…”
Section: Resultsmentioning
confidence: 99%